1998
DOI: 10.1093/humrep/13.5.1175
|View full text |Cite
|
Sign up to set email alerts
|

Circulating antibodies to a conserved epitope of the Chlamydia trachomatis 60 kDa heat shock protein (hsp60) in infertile couples and its relationship to antibodies to C.trachomatis surface antigens and the Escherichia coli and human HSP60

Abstract: To evaluate the relationship between immunity to specific regions of the Chlamydia trachomatis 60 kDa heat shock protein (hsp60), autoimmunity to human HSP60 and infertility, sera from 50 women and 45 men seen for an infertility evaluation were tested. Humoral immunity to human HSP60 was detected in 18% of women and 8.9% of men while antibodies to the Escherichia coli hsp60 were detected in 12% of women and 4.4% of men. These differences were not statistically significant. In contrast, antibodies to a syntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 20 publications
0
27
0
1
Order By: Relevance
“…In one study, cHsp60 serum antibodies were shown to be the best predicting factor for tubal factor infertility (51). Mapping of cHsp60-1 peptide epitopes in human sera has been done (50,54); it may be worthwhile to investigate whether peptides of cHsp60-2 and/or cHsp60-3 contribute to the generation of specific immunoglobulins. GroEL proteins are essential for bacterial growth and ensure that newly synthesized proteins are functional; expression of GroEL proteins increases in response to a variety of stresses, including heat shock and nutrient deprivation (56).…”
Section: Discussionmentioning
confidence: 99%
“…In one study, cHsp60 serum antibodies were shown to be the best predicting factor for tubal factor infertility (51). Mapping of cHsp60-1 peptide epitopes in human sera has been done (50,54); it may be worthwhile to investigate whether peptides of cHsp60-2 and/or cHsp60-3 contribute to the generation of specific immunoglobulins. GroEL proteins are essential for bacterial growth and ensure that newly synthesized proteins are functional; expression of GroEL proteins increases in response to a variety of stresses, including heat shock and nutrient deprivation (56).…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, it has been shown earlier that antibodies to the conservative peptide of C trachomatis Hsp60 are associated with autoimmunity to human Hsp60 and with infertility as chronic sequelae of C trachomatis infection. 26 Unfortunately, the role of the corresponding peptide of C pneumoniae Hsp60 in autoimmunity and in the development of atherosclerosis has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…This has largely resulted from a body of literature demonstrating high-titer human antibody responses to cHSP60 in patients with tubal pathology and additionally that, in several animal models, tissue pathology developed after repeated inoculations with cHSP60 protein (reviewed in reference 138). However, this mechanism is a subject of considerable controversy because of inconsistencies between the different published findings, i.e., problems with protein preparations that involved a hypersensitive detergent being used in some animal models and cross-reactivity or poor specificity of some of the antibody tests (141)(142)(143)(144)(145)(146)(147). On the other hand, there is no doubt that cHSP60 is a predominant chlamydial antigen that does frequently elicit an immune response.…”
Section: Chsp60-induced Delayed Hypersensitivitymentioning
confidence: 99%